PEMANFAATAN LIMBAH KULIT PISANG SEBAGAI MASKER KECANTIKAN ORGANIK - Nuriasih, Putu Dhea; Putra, I Kadek Kriss Adi Giri; Asih, Ni Komang Tinggal; Pratiwi, Luh Putu Kirana (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
This study aims: (1) To preserve the environment by utilizing banana peels waste into masks and knowing how to make them; (2) For people to switch from chemicals to natural materials such as banana peel waste; (3) In order to find out the marketing strategy of face masks from waste. The method of implementation uses descriptive methods. Data collected through observation. The results showed that the process of making a banana skin mask using 100 kg of banana skin waste produced 65 products of Nuri Glow Face Mask at a price per product of 45,000, banana peel waste containing zerotin which serves to improve mood, reduce pain on the face because it contains a number of vegetable oils, banana peels contain anti-fungal substances that can prevent bacteria from multiplying and acidic properties and also sepah which serves to reduce excess oil on the face, accelerate the fading of scars, because basically banana peels contain a number of vitamin C. Nuri Glow Face Products Mask addressed to high school teenagers and students. The marketing area of this banana skin mask is only marketed in the Denpasar area.